Resident physicians’ mental health during COVID-19: Advocating for supports during and post pandemic - Gregory, Emma (Canadian Medical Education Journal, 2020)
There is already considerable evidence of how this novel corona virus (COVID-19) has had a major impact on our mental health and wellbeing. We are reminded of the mental health consequences of previous infectious disease outbreaks, not only for the public, but for frontline healthcare workers. Yet the lived experiences of resident physicians are missing from this discussion despite them being essential to the COVID-19 response and continuing to provide care during this time. The author asserts that considering what is known about the mental health effects of frontline healthcare work during previous outbreaks, residents are at risk given their role as physicians. In addition to baseline systemic stressors that put residents at risk of mental distress, they also face COVID-19 related stressors that exacerbate the risk given their role as trainees too. The author acknowledges and welcomes several rapid responses to residents’ developing mental health needs from medical leaders across Canadian hospitals, programs, and resident bodies. Ultimately, however, medical leaders need to advocate for and implement changes that will support residents’ mental health now and in the long-term well after COVID-19 has left its mark.